Analysis of Platelet Index in Various Classifications of Hypertension in Pregnancy - Wahyudi, Nanda; Ibrahim, Fatmawati; Anggraeni, Ni Made Dewi (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
Hypertension in pregnancy is the fourth largest cause of maternal mortality in Indonesia. One classification of hypertension in pregnancy is preeclampsia. Thrombocytopenia is the most important sign indicating the severity of preeclampsia. 50% of preeclampsia cases are associated with thrombocytopenia. The aim of study is to analyze the Platelet Index in preeclaampsia dan severe preeclampsia. This research used cross sectional and collecting platelet index data from medical records of patients with preeclampsia and severe preeclampsia, in RSUD Dr. Aloe Saboe Gorontalo, January 2020 - December 2023. The sample is 30 medical records of pregnant women who were diagnosed preeclampsia and severe preeclampsia. Used simple random sampling technique. The statistical analysis used Independent T test. Results: The average platelet level in pregnant women with preeclampsia is 252.6, and severe preeclampsia is 191.467. P value = 0.012 (<0.05) this shows that there is a difference in the average of the preeclampsia and severe preeclampsia groups. Conclusion: The platelet index in the preeclampsia group was greater than in the severe preeclampsia group